PENGARUH KONSENTRASI KOLKHISIN TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L.) - Sinaga, Eka Juliyanti; Bayu, Eva Sartini; Hasmawi Hasyim, Hasmawi (Universitas Sumatera Utara, 2014)
The Effect of Cholchisine Consentration to Growth and Produduction Green Beans (Vignaradiata L.) supervised by EVA SARTINI BAYU and HASMAWI HASYIM. One of thebreeding program that can be used to developed new varieties by using breeding mutation thatusing by colchisine consentration. The experiment had been conducted at Tumpatan NibungBatangkuis, Deli Serdang, Sumatera Utara (± 25 metres asl) during March until Juny 2012nd byusing randomized block design that were K0 (0%); K1 (0,04 %); K2 (0,08); K3 (0,12%); K4(0,16%) and then continued with Duncan's Multiple Range Test (DMRT). The parameters weregermination percentage, plant height, leaf numbers, flower ages, weight of pods dry ,number ofpods containing, number of seeds in each pods and 100 seeds weight. The result showed thatapplication colchisin significantly effected on growths: plant height and number of leafs, andalso production parameters such as: flower ages, weight of pods dry, number of pods containing,and number of seeds in each pods.Keywords: green beans, cholchisine